2020
DOI: 10.3389/fphar.2020.604314
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I, Randomized, Double-Blind, Placebo-Controlled, Single Ascending Dose, Multiple Ascending Dose and Food Effect Study to Evaluate the Tolerance, Pharmacokinetics of Jaktinib, a New Selective Janus Kinase Inhibitor in Healthy Chinese Volunteers

Abstract: Background: Jaktinib is a novel selective janus kinase 1/2 inhibitor. The phase I first-in-human study evaluated the tolerance and pharmacokinetics of jaktinib in healthy Chinese subjects.Methods: A randomized, double-blind, placebo-controlled study were designed. A total of 126 healthy subjects were enrolled into the single ascending dose, multiple ascending dose and food effect study. Safety endpoints included adverse events, abnormal vital signs, 12-lead ECGs, abdominal ultrasound, chest x-ray, physical exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…It displays similar potency to Momelotinib and Ruxolitinib [193]. Jaktinib suppresses Jakl, Jak2, Jak3 and Tyk2 at the cellular level, inhibits the Jak-Stat signaling pathways to block the release of cytokines, including IL-2, IL-4, IL-6, IL-7 and IL-10, and significantly relieves inflammation due to immune reactions [193]. Preclinical toxicology studies conducted in Wistar rats and Beagle dogs with oral administration of Jaktinib showed no observed AEs [193].…”
Section: Jaktinib (Suzhou Zelgen Biopharmaceuticals)mentioning
confidence: 93%
See 3 more Smart Citations
“…It displays similar potency to Momelotinib and Ruxolitinib [193]. Jaktinib suppresses Jakl, Jak2, Jak3 and Tyk2 at the cellular level, inhibits the Jak-Stat signaling pathways to block the release of cytokines, including IL-2, IL-4, IL-6, IL-7 and IL-10, and significantly relieves inflammation due to immune reactions [193]. Preclinical toxicology studies conducted in Wistar rats and Beagle dogs with oral administration of Jaktinib showed no observed AEs [193].…”
Section: Jaktinib (Suzhou Zelgen Biopharmaceuticals)mentioning
confidence: 93%
“…Jaktinib is an oral and potent Jak1/2 inhibitor with an IC50 of 0.1 µM based on a cellfree kinase assay (Table 1). It displays similar potency to Momelotinib and Ruxolitinib [193]. Jaktinib suppresses Jakl, Jak2, Jak3 and Tyk2 at the cellular level, inhibits the Jak-Stat signaling pathways to block the release of cytokines, including IL-2, IL-4, IL-6, IL-7 and IL-10, and significantly relieves inflammation due to immune reactions [193].…”
Section: Jaktinib (Suzhou Zelgen Biopharmaceuticals)mentioning
confidence: 99%
See 2 more Smart Citations
“…Jaktinib (Suzhou Zelgen Biopharmaceuticals Co., Ltd.) is a twice-daily, oral selective JAK1/2 inhibitor currently in phase II development for psoriasis (Table 2) [61]. The drug was Pustulosis Area and Severity Index, mNAPSI Modified Nail Psoriasis Severity Index investigated in a phase I single ascending dose (SAD), multiple ascending dose (MAD), and food effect study and was found to be well tolerated among healthy Chinese participants [61].…”
Section: Janus Kinase Inhibitorsmentioning
confidence: 99%